STRATEGI PROMOSI WISATA PADA DINAS PARIWISATA KABUPATEN MAMASA - Idastin Idastin; Muhammad Abid (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2020)
This study aims to determine the tourism promotion strategy at the Mamasa Regency Tourism Office. This research use desciptive qualitative approach. Data collection techniques obtained from observation, interviews and documentation. The results of his research show that the seven main strategies carried out by the Mamasa Regency Tourism Office have been implemented but all of them have not run optimally so the desired results have not been achieved according to the target. This is due to inhibiting factors, namely insufficient facilities and infrastructure; human resources are still lacking; lack of regulations and a strong legal basis to regulate Mamasa tourism; and forms of overlapping management between government, foundations or families and the private sector.